Evaluation of maize genotypes for locating sources of resistance to Exserohilum turcicum, incitant of turcicum leaf blight of maize - and SANGAM LAL, RAM DUTTA, MEENA SHEKHAR* (Indian Phytopathology, 2005)
Twenty-six elite maize inbred lines were screened under the glass house condition to three representative isolates/proposed races (Races-2, 3 and 4) of Exserohilum turcicum collected from various maize growing regions of India. Of these, three inbred lines CM 104, CM 105 and CM 118 were found resistant against all the three races. CM 212, CM 300 and LM 5 found resistant against Race-2 and Race-3. CM135 found against Race-3.